Raw Hard Clam as Adsorbent to Remove Phosphate in Water: Removal Prediction, Kinetic and Isotherm Model Study - Norzainariah Abu Hassan; Sheikh Farhan Bakatal, Sheikh Muhammad Fadhlullah Baktal; Mohamed Mubarak Ali , Muhammad Sharif; Ramle, Yasmin Raihana; Muslim, Nur Husna; Abdullah, Noorul Hudai; Radin Mohamed, Radin Maya Saphira; Nur Atikah Abdul Salim (International Journal of Integrated Engineering, 2025)
Phosphorus pollution from various sources like agriculture, untreated industry, and domestic wastewater is a significant cause of water contamination. It can trigger eutrophication, marked by an excessive supply of nutrients that fuel the rapid growth of algae and aquatic plants. This, in turn, can lead to harmful algal blooms, severely reducing oxygen levels in the water and affecting marine life, including fish and other creatures suffering from the lack of oxygen. The purpose of this study is to evaluate how effectively raw hard clam shells remove phosphate from synthetic wastewater through batch experimental testing. Batch experiments were conducted using raw hard clam shells (particle sizes 1.18 to 2.36 mm) mixed in an orbital shaker at 170 rpm using potassium dihydrogen phosphate solution, 100 mL at a particular time, until an equilibrium state. The batch experiment data evaluating phosphate removal from raw hard clam shells had the highest removal effectiveness of 99.6%. The kinetic study proves that the predominant adsorption mechanism between the adsorbent and adsorbate involves chemisorption, where electron sharing occurs, forming chemical bonds. The adsorption isotherm data showed suitability for the Langmuir model, indicating that adsorption happens at particular binding sites in monolayer adsorption on the adsorbent surface. Additionally, the data can be used to understand the prediction contour of mass of adsorbent required and removal efficiency under various beginning concentrations from research using batch experiments. The significant potential of this study is that the Raw Hard Clam Shells adsorbent is a sustainable and eco-friendly material for tackling phosphate pollution in future wastewater treatment.